2015
DOI: 10.1002/lsm.22398
|View full text |Cite
|
Sign up to set email alerts
|

Healing of chronic wounds with adjunctive ablative fractional laser resurfacing in two pediatric patients

Abstract: The combination of tolerability and efficacy observed in these cases introduces AFR as a potential promising adjunct to existing treatments for chronic, non-healing wounds in the pediatric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Similarly, Vaderhobli et al [15] and Cercadillo‐Ibarguren et al [16] reported a width <200 μm in an incision of porcine tongue with the microsecond pulsed‐mode CO 2 laser at 0.2–3.5 W. Therefore, the use of ultrapulsed CO 2 laser can permit true “micron‐level” tissue debridement, achieving wound treatment with an unprecedented precision. Meanwhile, CO 2 laser may play a role in hemostasis, and control of local infection during the treatment of skin wounds [6–9] to promote faster wound healing. Therefore, it could serve as a more effective debridement than traditional surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Vaderhobli et al [15] and Cercadillo‐Ibarguren et al [16] reported a width <200 μm in an incision of porcine tongue with the microsecond pulsed‐mode CO 2 laser at 0.2–3.5 W. Therefore, the use of ultrapulsed CO 2 laser can permit true “micron‐level” tissue debridement, achieving wound treatment with an unprecedented precision. Meanwhile, CO 2 laser may play a role in hemostasis, and control of local infection during the treatment of skin wounds [6–9] to promote faster wound healing. Therefore, it could serve as a more effective debridement than traditional surgery.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have found that the carbon dioxide (CO 2 ) laser can be used not only for scar treatment [3,4], but also for wound debridement and treatment [5–11]. However, at present, the application of CO 2 laser in the treatment of chronic wounds has been few documented, mostly in case reports.…”
Section: Introductionmentioning
confidence: 99%
“…100 Prolonged and dysregulated inflammation is a major contributing factor to impaired ulcer healing. 101 The period of skin degradation before ulcer formation makes chronic wounds somewhat predictable, and also presents a potential window of opportunity for the application of prophylactic measures to prevent ulceration. This is not a new concept-various modalities such as barrier creams, compression therapy, and preventative offloading are routinely applied clinically for ulcer prevention by reducing the harmful impacts of external stressors on the skin.…”
Section: Potential Utility In Chronic Wound Preventionmentioning
confidence: 99%
“…In an interesting case series two pediatric patients with chronic wounds within scars showed rapid healing with a singlepass treatment by fractionated carbon dioxide (CO 2 ) laser [46]. In another case series done by Phillips et al, CO 2 laser was used in the treatment of posttraumatic slow healing wounds in three elderly patients.…”
Section: Co 2 Laser and Wound Healingmentioning
confidence: 99%